Determination of the best method for processing gambier liquid by-product [Uncaria gambir (hunter) roxb] as natural antioxidant sources - Ismail, A. S.; Rizal, Y.; Armenia, A.; Kasim, A. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
The study was conducted to determine the best gambier liquid by-product (GLB) processing methods based on antioxidant activity as natural antioxidant sources. The processing methods were A (ethyl acetate fractionation), B (oven drying) and C (freeze drying) methods. The observed variables were dry extract (using weighing method), tannin (using hide powder method), catechin (using SNI 01- 339-2000 method), total phenol (using folin ciocalteu reagents) and antioxidant activities (DPPH method) based on ICAO50. These antioxidant activities were compared with vitamin C as a positive control. The results indicated that the different processing methods significantly affected (P<0.05) dry extract, tannin, catechin, total phenol and antioxidant activity of GLB. The highest dry extract, tannin, catechin, total phenol, and antioxidant activity from GLB were at treatment B (10.76%), B (39.69%), A (86.07%), C (80.97 mg GAE/g), and C (ICAO50 2.74 µg/mL), respectively. The antioxidant activity on treatment C was not different from vitamin C antioxidant activity (2.88µg/mL). Thus, the treatment C (freeze drying method) was the best method to process GLB based on antioxidant activity as natural antioxidant sources.